Design procedures for installation of suction caissons in clay and other materials - Houlsby, G; Byrne, B (2005)
Suction-installed skirted foundations, often referred to as suction caissons, are increasingly being used for a variety of offshore applications. In designing a caisson a geotechnical engineer must consider the installation process as well as the in-place performance. The purpose of this paper is to present calculation procedures for the installation of a caisson in clay. For clay sites, the caisson will often be used as an anchor, with the ratio of the skirt length (L) to the diameter (D) as high as 5. Calculation methods are presented for determining the resistance to penetration of open-ended cylindrical caisson foundations with and without the application of suction inside the caisson. Comparisons between predictions and case records are made. A companion paper describes the calculation procedure for installation in sand soils. Finally, comments are made here about installation in a variety of soils other than homogeneous deposits of clay or sand.